THE EFFECT OF APPLICATION OF FLIPPED LEARNING MODEL MODIFICATION TO SELF CONFIDENCE IN CHILDREN AGED 5-6 YEARS IN TK NURUL ZAMAN BATHIN SOLAPAN DISTRICT OF BENGKALIS DISTRICT - sri rahwani; febrialismanto febrialismanto (Program Studi Pendidikan Guru PAUD Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2020)
Based on field observations it can be seen that the level of confidence in children aged 5-6 years is still in the low category, so it is necessary to use a modified flipped learning model. This study aims to determine the effect of the flipped learning model on self-confidence in children aged 5-6 years in Nurul Zaman Kindergarten, Bathin Solapan District, Bengkalis Regency. This study used an experimental method with one group pretest posttest design with a population of 23 children using saturated samples (entire population) 23 and using saturated sample techniques. Data collection techniques in this research are observation techniques. The data analysis technique used t-test using the SPSS 23 program. The results of data analysis can be obtained t count 42,339 greater than t table 2,074 with a singification of 0,000 <0.05. It can be concluded that there are differences in the level of confidence before and after the introduction of the modified flipped learning model. The effect of the modified flipped learning model based on the N Gain formula of 76.63% is in the high category. Berdasarkan hasil pengamatan dilapangan dapat diketahui bahwa tingkat kepercayaan diri pada anak usia 5-6 tahun masih dalam kategori rendah, sehingga perlu penggunaan model flipped learning modifikasi. Penelitian ini bertujuan untuk mengetahui pengaruh model flipped learning terhadapa kepercayaan diri pada anak usia 5-6 tahun di TK Nurul Zaman Kecamatan Bathin Solapan Kabupaten Bengkalis. Penelitian ini menggunakan metode eksperimen dengan desain one group pretest posttest dengan jumlah populasi 23 orang anak menggunakan sampel jenuh (seluruh populasi) 23 dan menggunakan teknik sampel jenuh. Teknik pengumpulan data dalam [eneitian ini adalah teknik observasi. Teknik analisis data menggunakan uji t-test dengan menggunakan program spss 23. Hasil analisis data dapat diperoleh t hitung 42.339 lebih besar dari t table 2,074 dengan singnifikasi 0,000<0,05. Dapat disimpulkan bahwa terdapat perbedaan tingkat kepercayaan diri sebelum dan sesudah penerepan model flipped learning modifikasi. Pengaruh yang diberikan model flipped learning modifikasi berdasarkan rumus N Gain sebesar 76,63% berada pada kategori tinggi.